2022
DOI: 10.1101/2022.01.04.475006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards transboundary networks of climate-smart marine reserves in the Southern California Bight

Abstract: Climate-smart conservation addresses the vulnerability of biodiversity to climate change impacts but may require transboundary considerations. Here, we adapt and refine 16 biophysical guidelines for climate-smart marine reserves for the transboundary California Bight ecoregion. We link several climate-adaptation strategies (e.g., maintaining connectivity, representing climate refugia, and forecasting effectiveness of protection) by focusing on kelp forests and associated species. We quantify transboundary larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…In contrast, BSB larval recruitment is limited to the mainland coast and given its sporadic nature and more southerly larval distribution in the SCB, may be influenced more so by sporadic northward advection of larvae from Baja California as has been suggested for other fishery species in the region (Smith & Moser 1988, Allen & Franklin 1992, Ben-Aderet et al 2020). This too has implications with respect to harvest impacts and climate change, as future transboundary connectivity between the SCB and Mexico is predicted to be significantly reduced (assuming decreased PLDs and lower kelp persistence), thus highlighting the importance of protecting habitats important for larval connectivity and binational conservation efforts to manage the collective resource (Arafeh-Dalmau et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, BSB larval recruitment is limited to the mainland coast and given its sporadic nature and more southerly larval distribution in the SCB, may be influenced more so by sporadic northward advection of larvae from Baja California as has been suggested for other fishery species in the region (Smith & Moser 1988, Allen & Franklin 1992, Ben-Aderet et al 2020). This too has implications with respect to harvest impacts and climate change, as future transboundary connectivity between the SCB and Mexico is predicted to be significantly reduced (assuming decreased PLDs and lower kelp persistence), thus highlighting the importance of protecting habitats important for larval connectivity and binational conservation efforts to manage the collective resource (Arafeh-Dalmau et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, BSB larval trends may be more influenced by seeding from Baja California, Mexico (a region with relatively higher BSB larval abundance). Arafeh-Dalmau et al (2022) demonstrated transboundary larval connectivity between the SCB and northern Baja California of several hundred kilometers (e.g., ~400 km north from Mexico to California in summer and winter and ~400 km from the SCB to northern Baja California throughout the year), and this dispersal was important to species with a longer pelagic larval duration (PLD), like that of BSB and KB (~ one lunar month, Findlay & Allen 2002).…”
Section: Species-specific Differences In Bass Larval Abundance Trendsmentioning
confidence: 99%
See 1 more Smart Citation